Reframing global governance: apocalypse soon or reform! (2008)
In this article, the author describes and supports with evidence the three global issues that require the most urgent solution. Then he explains the challenges in governance that it is necessary to overcome for the solution of such problems. After describing the contemporary trends in global governance, the article proposes some ways to strengthen it while citizenship and democracy become mutually strengthened. Lastly, the article warns us on the urgency in the implementation of such reforms to avoid facing a current or soon apocalypse.